Kontribusi Hukum Islam dalam Mewujudkan Good ‎Governance di Indonesia - M. Hasan Ubaidillah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The article describes the contribution of Islamic law in implementing good governance in indonesia. Good governance is a campaign to achieve prosperous and secure based on rule of law. The law which is just and egalitarian whose priority is to uphold the betterment to all citizens. In Islamic law, the maxim saying that the policies of the government must be intended to uplift people’s prosperity (tasarruf al-ra’iy ‘ala al–ra’iyyah manut bi al-maslahah) is a basis for good governance. The article concludes that contribution of Islamic law in creating good governance in Indonesia is based of the principle of betterment to all citizens. Such a principle is founded upon the enforcement of five basic principles (al-usul al-khamsah) that are ; hifz al-din, hifz al–nafs, hifz al-’aql, hifz al-nasl dan hifz al–mal. These five basic principles are in line with the goals and visions of Indonesian national development of 2020 which have been commanded by the MPR decision No. 8 of 2001. The goals are the creation of Indonesian community that are religious, civilized, unified, democratic, just, prosperous, advanced, self-sufficient with good and clean governance.